DEVELOPMENT OF INDONESIAN EARTHQUAKE RISK MAP AS A REFERENCE TO NATIONAL MITIGATION AND DISASTER RISK REDUCTION STRATEGIES - Lambang Goro, Garup
Various countries data compiled by UNISDR (United Nation Office for Disaster Reduction) states that the highest number of fatalities was the result of geophysical disasters (earthquakes, tsunamis and volcanoes) although those low frequency of occurrence. Meanwhile, Indonesia was in the third highest position after Japan and the United States for the average economic loss due to the earthquake. The significance of earthquake hazard studies in Indonesia has been started since 1983 and continues to develop until now with various improvements, both in the aspect of updating earthquake source data, selecting the latest GMPE (Ground Motion Prediction Equation), and its analysis methods. The latest earthquake hazard and source maps were published in 2017. Meanwhile, studies related to earthquake risk were carried out by the National Agency for Disaster Management (BNPB) in 2011 and developed in 2016 by considering the site-specific. Those risk map is presented in the form of a risk index (low, medium and high), and does not take into account the vulnerability of the building so it does not present the actual loss value. Address the isuue, it is necessary to carry out an earthquake risk study in consideration of the updated of the earthquake sources, GMPE’s, site-specific soil conditions, exposure and vulnerability of buildings, hence a more adequate map of the value of building losses due to earthquakes was produced The research stages began with Hazard Analysis using the Classical PSHA method to produce a hazard map presented in an earthquake peak acceleration map in bedrock (SB) and on the surface, in a period of 0 seconds (PGA), 0.2 seconds SA (0.2) and 1.0 sec SA (1.0) for the probability of being exceeded by 10% and 2% in 50 years respectively , continued with the calculation of the amplification factor and the results were compared to the amplification factor value in the Building Code (SNI-1726-2019). The next step is the comparison of the Classical PSHA method with the Event-Based PSHA method in order to determine the adequate SES (Stochastic Event Set) value which is then used for risk analysis input using the Event-Based Risk Analysis method. The results of Hazard analysis using the Classical PSHA method in bedrock (SB) in a period of 0 seconds (PGA), 0.2 seconds SA (0.2) and 1.0 seconds SA (1.0) for the probability of exceedance of 10% and 2% in 50 years respectively indicates conformity with the 2017 Indonesia Earthquake Source And Hazard Map for the same period and probability of exceedance. The amplification factor of the calculation results corresponds to the value in SNI-1726-2019 for almost all site classes. For the comparison between the Classical PSHA and the Event-Based PSHA methods, the results show that the greater the SES value, the smaller the standard deviation value. Consider to the similarity of map comparisons and standard deviation values, SES=50000 and SES=200000 are used for the probability of exceeding 10% and 2% in 50 years respectively for risk analysis using the Event-Based method. The method of determining the building structure taxonomy based on floor type data from BPS 2010 can be used for earthquake risk analysis at the national level, after verification with the visual survey through the street view facility on Google Maps for an urban area, which produce an acceptable percentage value for every structural buildings type The results of the risk analysis show that the highest total loss of building structures due to earthquake per regency / municipality is dominated in areas at Java Island; this is very possible due to the high density of buildings and population in Java. The total building loss due to the earthquake per Regency / municipality for residential buildings is estimated to reach a maximum of Rp. 56.5 Trillion at a return period of 475 years and Rp. 170.9 Trillion for a return period of 2475 years. In commercial buildings the structural loss due to the earthquake is predicted to reach a maximum of Rp. 44 Trillion for the return period of 475 years and Rp. 147 Trillion for a return period of 2475 years, while for industrial buildings the maximum loss is Rp. 3.8 Trillion for a return period of 475 years and Rp. 12 Trillion for a return period of 2475 years. With the compilation of the Map of Total Building Losses due to the Earthquake per Regency / Municipality for exposure: residential buildings, commercial buildings and industrial buildings, it can be used as a reference for preparing disaster mitigation and readiness for the community and the government, particularly the Disaster Management Agencies.